Method Of Projects Training A Teacher In The System Of Professional Education - Kurbonov Bakhodir Ergashevich (The American Journal of Social Science and Education Innovations, 2021)
The article examines the importance of using the project method as an educational technology in the development of the competencies of university students. The article analyzes the relationship between the features of project education and the effectiveness of professional training of university students.